Assessment of The Reliability of Cognitive (Attention and Memory) Tests (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. Special neuropsychological tests, which are used to assess cognitive functions in clinical practice, are often complicated, time-consuming, demanding special knowledge and expensive; therefore, cognitive functions frequently remain insufficiently assessed. For this reason, our selected and validated tests intended for the assessment of short-term memory and attention could be successfully applied in sports and clinical rehabilitation. Research aim. The aim of this study was to assess the reliability of the tests of cognitive functions (memory and attention). Research methods. The reliability of the tests was assessed using the intraclass correlation coefficient (ICC) and variation coefficient (VC). Young and healthy students (n = 41), aged from 18 to 30 (24.6  ± 2.3), participated in the research. The participants accomplished the tests 4 times, i. e. 2 times (with a one-hour break) on the first day (teaching) and 2 times (with a one-hour break) on the second day (reliability testing). Research results. The results of testing the volume of spatial memory and even number recognition ranged from high to very high reliability of the tests. The results of ICC single of testing memory for figure recognition demonstrated  low  reliability,  whereas  ICC  average  proved  average  reliability.  The  results  of  complex  reaction assessment, search for image samples and attention transfer ranged from high to a very high reliability of the tests. Discussion and conclusions. The reliability of the tests of memory and attention assessment is high (with the exception of figure recognition tests, the reliability of which is average/low); therefore, the tests are suitable to be used in sport and  clinical rehabilitation practice, aiming at determining the changes in cognitive functions under the influence of external factors, e. g. cold, heat, etc.Keywords: brain functions, validity, stability, testing.